Sociodemographic Factors Associated with Stunting Cases Among Tobacco Plantation Society in Jember District, Indonesia: Faktor Demografi dan Sosial Terkait Kasus Stunting di Masyarakat Perkebunan Tembakau Kabupaten Jember, Indonesia - Dewi Rokhmah; Anita Dewi Moelyaningrum; Isa Ma'rufi; Ninna Rohmawati; Khoiron (Universitas Airlangga, 2022)
Background: Social and Demographic can affect health status. Social institutional factors such as cultural factors, traditions, and habits that exist in society can lead to the emergence of nutritional problems experienced by toddlers. This can have an impact on the growth and development of infants. Objectives: The study aims to analyze the relationship between social institutions and the incidence of stunting in communities in tobacco plantations in Jember Regency. Methods: This research is an observational analytic study, using Cross Sectional Design. The population of this study is families who have children under five with nutritional problems (nutrient-prone) in the district area which is a tobacco-producing center in Jember Regency. The sample in this study amounted to 233 respondents. Data were collected by interview using a questionnaire. The collected data were analyzed descriptively. The statistical test used in this study to test the hypothesis is Chi-Square. Results: There is a relationship between the type of work of the mother and stunting (p= 0.015 <α). Mothers who do not work have a chance of 0.955 times or 1 / OR = 1.047 times greater for not having children who are stunted. There is a relationship between multiple institutions that includes two variables that had a significant association with the nutritional status of children, which is the variable Institution and institutions Education Information Hope and Institution Somatic Hope. Mothers who support related to health care have the opportunity 0,235 or 1 / OR = 4,255 times to not have a stunted child. Conclusions: Mother is an important factor to prevent stunting.